(untitled) (International journal of artificial intelligence, 2025)
This study explores the process of decision-making in non-situational contexts and examines its long-term psychological consequences. In non-situational contexts, individuals are required to make decisions without the presence of clear situational cues or prior experiences, often leading to uncertainty and emotional distress. This research investigates the cognitive, emotional, and social factors that influence decision-making in these complex situations. Furthermore, it seeks to understand the psychological outcomes of such decisions over time, particularly how individuals adapt to and cope with the consequences of their choices. The study emphasizes the importance of psychological resilience, emotional regulation, and cognitive flexibility in mitigating negative long-term effects. By integrating theoretical models from cognitive psychology, emotional intelligence, and decision theory, this research aims to provide insights into how decision-making under uncertainty can impact individuals' mental health and well-being in the long run. The findings have implications for developing strategies to improve decision-making skills, particularly in high-stress and unpredictable environments, and for enhancing psychological interventions aimed at promoting emotional recovery and cognitive adaptation.